The Market for political economy : the advent of economics in British university culture, 1850-1905 - Kadish, Alon, 1950-; Tribe, Keith (Routledge, 1993)
Why did political economy become pre-eminent in the emergence and development of the social sciences? From a relatively early stage in its development political economy was accepted as a legitimate, if minor, part of a general liberal education. However, economic science did not become firmly rooted in the academic curriculum of the modern English university until after the first world war. The Market for Political Economy argues that whilst it is commonly assumed that the complexities of a modern industrial economy would require a greater number of trained economists, the actual demand amongst.